Nitrosoalkenes: Underappreciated Reactive Intermediates for Formation of Carbon–Carbon Bonds - Weinreb, Steven M. (Synlett, 2019)
This Account describes studies carried out by my group during the past decade on both intra- and intermolecular conjugate additions of carbon nucleophiles to nitrosoalkenes. Using the Denmark protocol for the generation of nitrosoalkenes from α-chloro-O-silyloximes, a number of bridged and fused bicyclic ring systems can be prepared via the intramolecular version of this process. Intermolecular conjugate addition reactions of nitrosoalkenes with a wide variety of ester enolates as coupling partners can also be achieved efficiently using a similar procedure. Some stereochemical aspects of these nucleophilic additions have been studied with both acyclic and cyclic nitrosoalkenes. This methodology has been applied as key steps in synthetic approaches to some complex indole and Myrioneuron alkaloids.1 Introduction2 Conjugate Additions of Nitrosoalkenes2.1 Background2.2 Intramolecular Reactions2.3 Intermolecular Reactions2.4 Stereochemical Aspects3 Applications to Natural Product Synthesis3.1 Angustilodine and Related Alkaloids3.2 Approach to Apparicine-Type Alkaloids3.3 Myrioneurinol4 Summary and Outlook
Keywords: conjugate additions; alkaloid synthesis; total synthesis; enolonium ion equivalent; umpolung; indole alkaloids; Myrioneuron alkaloids